BRCA1 Gene Q356R (1186A=G) Polymorphism and Epithelial Ovarian Cancer Incidence - Rakhmatsyah, Benyamin; Saleh, Agustria Z; Sanif, Rizal; Yuwono, Yuwono (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To determine the association between BRCA1 gene Q356R (1186A=G) polymorphism and epithelial ovarian cancer incidence. Methods: This study is an observational analytic study with casecontrol study design. All patients diagnosed with epithelial ovarian cancer that were treated in the outpatient clinic and inpatient ward of the Department of Obstetrics and Gynecology, Dr. Mohammad Hoesin Hospital, Palembang who met the inclusion criteria were included in this study. DNA extraction was performed on blood samples, followed by PCR-RFLP process. Results: We obtained the genotype distribution of BRCA1 Q356R (1186A=G) polymorphisms to be QQ genotype (wild-type) on all 50 subjects in the case group (100%) and 50 control subjects (100%). Similarly, all BRCA1 alleles have the Q allele. The results of this study found no polymorphism of the BRCA1 Q356R (1186A=G) in the ovarian cancer and control groups. Conclusion: Polymorphism of BRCA1 gene Q356R (1186A=G) was not significantly associated with epithelial ovarian cancer incidence. [Indones J Obstet Gynecol 2015; 3-4: 206-211] Keywords: BRCA1 gene, epithelial ovarian cancer, polymorphism